Mango production knowledge and technological gaps of smallholder farmers in Amhara Region, Ethiopia - Dessalegn, Yigsaw; Assef, H.; Derso, T.; Tefera, M. (2014)
Mango production is steadily expanding in Amhara region, Ethiopia. However, its productivity is below the national average. A survey conducted in four representative districts of Amhara region using 70 randomly selected mango growers in order to assess mango production knowledge and technological gaps of smallholder farmers. Data collected through individual interview using semi-structured questioner and field observation, and analyzed using SPSS statistical software version 15. Majority (91.4%) of the respondents had less than 21 year mango production experiences. Further, 54.3% of the respondents did not attend formal education. Only 1.4 % of the respondents can do mango grafting. Majority of the respondents did not apply inorganic fertilizer, did not spray pesticides and fungicides to control pests and diseases, and did not prune their mango trees. These depict mango production knowledge and skill gaps of smallholder farmers. There is no site specific recommendation on irrigation interval, fertilizer rate, spacing, pruning season, scion and rootstock varieties, and insect pest and disease control methods for mango production. About 66% of the mango trees of the respondents are developed from seedlings and need to be converted into improved varieties through top-working. These indicate the existing technological gaps for mango production in the study area. Therefore, farmers need to be trained and improved mango production technologies should have to be introduced in order to improve the quality and boost the productivity of mango in the study area.